2014 Third Mediterranean Photonics Conference 2014
DOI: 10.1109/mephoco.2014.6866479
|View full text |Cite
|
Sign up to set email alerts
|

Rateless codes mitigation technique in a turbulent indoor Free Space Optics link

Abstract: Free Space Optics (FSO) links are affected by several impairments and, among them, optical turbulence is the most important factor that can degrade the link quality. Due to the presence of this phenomenon, the signal irradiance detected by the receiver fluctuates, thus causing erasure errors and fading events. In this work, we present an indoor Free Space Optics link, in which several turbulence conditions are generated by using two heating elements. We show that the generated turbulence causes erasure errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…To create a thermal gradient and hence to generate the turbulence we have used two 25 cm-long heating elements along the optical beam propagation path (OBPP) [10,11]. In [29,33,34] it has been experimentally demonstrated that turbulence can be generated over a short FSO link. A fan placed close to the collimator is used to generate the air flux towards the heating elements, in order to create more controlled and repeatable turbulence conditions.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…To create a thermal gradient and hence to generate the turbulence we have used two 25 cm-long heating elements along the optical beam propagation path (OBPP) [10,11]. In [29,33,34] it has been experimentally demonstrated that turbulence can be generated over a short FSO link. A fan placed close to the collimator is used to generate the air flux towards the heating elements, in order to create more controlled and repeatable turbulence conditions.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The rateless codes (RC) are the most recent software based solution [20][21][22][23][24][25][26][27][28][29], specifically designed for the erasure channels because of ease of operation and no rate mismatch as a result of imprecise channel estimation. RC have high potential for increasing the capacity of wireless systems in which the information is transmitted at a very high R and at the receiver it is accumulated in a form of graph, trellis, or matrix structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades the adequate use of renewable energy resources towards a sustainable development has been one of the most important issues faced by the scientific community [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In this context, Permanent Magnet Synchronous Machines have acquired great significance in the field of electrical drives and renewable energies, especially because of their great advantages in comparison with machines of the traditional type [17].…”
Section: Introductionmentioning
confidence: 99%
“…An important class of thin film solar cells consists of the CuInGa(S,Se)2 (CIGSSe) type, composed by Copper, Indium, Gallium, Sulfur and Selenide [1][2][3][4][5][6][7][8]. This low-power PV technology could be a significant alternative towards the traditional silicon photovoltaic modules, obtaining performances almost comparable to each other [9][10][11][12][13][14][15][16][17][18]. Indeed, because of their relatively good electro-optical properties, the thin film integrated PV have achieved adequate efficiencies.…”
Section: Introductionmentioning
confidence: 99%